2017
DOI: 10.1136/bmjopen-2017-016891
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy and effectiveness of 3D printing: a systematic review

Abstract: ObjectiveTo evaluate the clinical efficacy and effectiveness of using 3D printing to develop medical devices across all medical fields.DesignSystematic review compliant with Preferred Reporting Items for Systematic Reviews and Meta-Analyses.Data sourcesPubMed, Web of Science, OVID, IEEE Xplore and Google Scholar.MethodsA double-blinded review method was used to select all abstracts up to January 2017 that reported on clinical trials of a three-dimensional (3D)-printed medical device. The studies were ranked ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
134
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(140 citation statements)
references
References 40 publications
0
134
0
6
Order By: Relevance
“…1,2) Rapid prototyping is a common use of 3D printing to develop approaches for efficiently designing and manufacturing parts such as jigs and entire devices. Various medical devices 3,4) and imaging phantoms 5) have been produced using 3D printers. 3D printing of a surgical site is useful for understanding the pathology of the site before surgery and for aiding patient understanding of their condition prior to giving consent for surgery.…”
Section: Introductionmentioning
confidence: 99%
“…1,2) Rapid prototyping is a common use of 3D printing to develop approaches for efficiently designing and manufacturing parts such as jigs and entire devices. Various medical devices 3,4) and imaging phantoms 5) have been produced using 3D printers. 3D printing of a surgical site is useful for understanding the pathology of the site before surgery and for aiding patient understanding of their condition prior to giving consent for surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Other polymers without acid release and the release profiles of calcium and phosphorus ions from the scaffold should be investigated. Translation of this 3D P&P technology into the clinical realm, like any other translational tissue engineering technologies, must consider manufacturing, regulatory compliance, hospital procurement, and reimbursement [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…3D printing technology, also referred to additive manufacturing, has gained great attention in the medical field because of its potential benefits. 32,33 First, 3D-printed realsized models can give the surgeons better visualization and understanding of tumour anatomy. 20,34 Riggs et al 34 reported that they successfully printed a physical 3D-printed model to gain a better understanding of the complex cardiac structures as well as spatial relationship and extent of the tumour before surgery, so as to maximize the removal of the tumour while avoiding damage to critical structures.…”
Section: Discussionmentioning
confidence: 99%